Influence of probable respiratory sarcopenia on chronic lung diseases: a population-based cohort study of community-dwelling Chinese older adults - Yu, Haixia; Chen, Kangkang; Chen, Qifeng; Xu, Laichao (Frontiers in Medicine, 2025)
Background and objectivesThe impact of probable respiratory sarcopenia (RS) on the prevalence and incidence of chronic lung diseases (CLDs) in middle-aged and older adults remains poorly understood. This study utilized data from the China Health and Retirement Longitudinal Study (CHARLS) to explore this association.MethodsA total of 6,614 participants aged 45 and above were included in a cross-sectional analysis in 2011, and 5,630 participants were followed for 7 years for longitudinal analysis. Probable RS was defined as a coexistence of low respiratory muscle strength and reduced appendicular skeletal muscle (ASM) mass by a position paper by four professional organizations. CLDs were identified based on self-reported medical diagnoses, including asthma, chronic bronchitis, emphysema, and pulmonary heart disease. Statistical analyses included logistic and Cox proportional hazards regression models to assess the association between probable RS and CLDs, adjusted for a wide range of covariates.ResultsIn the cross-sectional analysis, probable RS [odds ratio (OR) = 2.18, 95% confidence interval (CI) = 1.84 ~ 2.58, p < 0.001], low ASM mass (OR = 1.79, 95% CI = 1.51 ~ 2.11, p < 0.001), and low respiratory muscle strength (OR = 2.76, 95% CI = 2.14 ~ 3.55, p < 0.001) were significantly associated with increased CLDs prevalence. In the longitudinal analysis, probable RS [hazard ratio (HR) = 1.49, 95% CI = 1.26 ~ 1.77, p < 0.001], low ASM mass (HR = 1.47, 95% CI = 1.25 ~ 1.73, p < 0.001), and low respiratory muscle strength (HR = 1.31, 95% CI = 1.09 ~ 1.57, p = 0.004) were associated with increased CLDs incidence.ConclusionProbable RS significantly influences the prevalence and development of CLDs among middle-aged and older adults. Early identification and targeted interventions to mitigate RS may reduce CLDs burden in this population.